2004
DOI: 10.1111/j.1349-7006.2004.tb03331.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of cisplatin, vinorelbine, and concurrent thoracic radiotherapy for unresectable stage III non‐small cell lung cancer

Abstract: To determine the recommended phase II dose of vinorelbine in combination with cisplatin and thoracic radiotherapy (TRT) in patients with unresectable stage III non-small cell lung cancer (NSCLC), 18 patients received cisplatin (80 mg/m 2 ) on day 1 and vinorelbine (20 mg/m 2 in level 1, and 25 mg/m 2 in level 2) on days 1 and 8 every 4 weeks for 4 cycles. TRT consisted of a single dose of 2 Gy once daily for 3 weeks followed by a rest of 4 days, and then the same TRT for 3 weeks to a total dose of 60 Gy. Fifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Therefore we conducted a phase I study of weekly cisplatin and vinorelbine with standard TRT. The studies described above 29,[31][32][33] reported that esophagitis and neutropenia were the major toxicities. The present study showed that the DLTs of our regimen were esophagitis, fatigue, infection, and hyponatremia.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore we conducted a phase I study of weekly cisplatin and vinorelbine with standard TRT. The studies described above 29,[31][32][33] reported that esophagitis and neutropenia were the major toxicities. The present study showed that the DLTs of our regimen were esophagitis, fatigue, infection, and hyponatremia.…”
Section: Discussionmentioning
confidence: 95%
“…32 In the cisplatin-vinorelbine arm, the doses reported by Masters et al 31 were used, and the CALGB concluded that induction chemotherapy followed by concomitant chemoradiotherapy was feasible, with the observed survival rates exceeding those of previous CALGB trials for all treatment arms. Sekine et al 33 conducted a phase I study and reported that the recommended dose of cisplatin was 80 mg/m 2 on day 1 and that of vinorelbine was 20 mg/m 2 on days 1 and 8 every 4 weeks with TRT including a 4-day interval. The Czech group 29 used the following schedule and dose: cisplatin 80 mg/m 2 on day 1 and vinorelbine 12.5 mg/m 2 on days 1, 8, and 15 every 4 weeks with standard TRT starting on day 4.…”
Section: Discussionmentioning
confidence: 98%
“…The other wellknown cisplatin-based regimen with concurrent radiotherapy is vinorelbine plus cisplatin. Because this regimen is considered to be safe and active regimen, it is currently often concurrently used with radiotherapy for locally advanced NSCLC (28,29). However, toxicity is well known to increase with greater myelotoxicity in such a concurrent treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas a full dose of the oldgeneration combination chemotherapy can be combined with concurrent radiotherapy, 4,5 a reduced-dose (weekly or daily administration) of new-generation chemotherapy must be used in combination with TRT. [8][9][10][11] Chemoradiation based on full-dose old-generation chemotherapy has not yet been directly compared with that based on reduced-dose new-generation chemotherapy. Well-designed multicenter clinical trials to determine how to integrate newer platinumbased regimens into chemoradiation protocols are thus urgently needed.…”
Section: Randomized Controlled Trials Of Chemoradiation Based On Newementioning
confidence: 99%